Characteristics of effective design support: insights from evaluating additive manufacturing design artefacts - Didunoluwa Obilanade; Peter Törlind; Christo Dordlofva (Design Science)
Evaluation approaches are needed to ensure the development of effective design support. These approaches help developers ensure that their design support possesses the general design support characteristics necessary to enable designers to achieve their desired outcomes. Consequently, evaluating design support based on these characteristics ensures that the design support fulfils its intended purpose.